2021
DOI: 10.1007/s00405-021-07068-x
|View full text |Cite
|
Sign up to set email alerts
|

Two Bonebridge bone conduction hearing implant generations: audiological benefit and quality of hearing in children

Abstract: Purpose The study aimed to evaluate audiological benefits, quality of hearing and safety of two Bonebridge generation: BCI601 and BCI602 (MED-EL, Innsbruck, Austria) in children. Methods Twelve children were implanted: five BCI601 and seven BCI602 comprising of ten conductive hearing loss, and two single sided deaf SSD subjects. Audiological outcomes tested were sound field audiometry, functional gain, speech recognition threshold (SRT50), speech recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(49 citation statements)
references
References 42 publications
2
46
0
1
Order By: Relevance
“…Notably, implantations with lifts could potentially result in skin dehiscence or wound infections due to extensive pressure on the skin by the elevated implant. However, as reported by previous studies, implantations with lifts were not associated with any complications in the BB601 1,3,5 nor in the new generation BB602, 10 which goes in hand with our current results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, implantations with lifts could potentially result in skin dehiscence or wound infections due to extensive pressure on the skin by the elevated implant. However, as reported by previous studies, implantations with lifts were not associated with any complications in the BB601 1,3,5 nor in the new generation BB602, 10 which goes in hand with our current results.…”
Section: Discussionsupporting
confidence: 88%
“…Besides noted studies, several case reports and case series could be identified, also reporting on satisfactory results after BB602 surgery. [8][9][10] Furthermore, 2 articles reported on the artifact reduction possibilities in magnetic resonance imaging by the new system BB602. 11,12 The aforementioned smaller dimension of BB602 simplifies the implant placement, even in demanding anatomical considerations.…”
mentioning
confidence: 99%
“…Several studies reported on the quality of life outcomes in BB adult subjects assessed by various measurement instruments, such as the abbreviated profile of hearing aid benefit (APHAB) and the Glasgow benefit inventory (GBI). All studies investigating the subjective benefit after BB implantation showed improvement in general, social, physical, and total function as measured by the GBI as well as high patient satisfaction paired with overall very low complication rates 19,45,46 . Investigating in addition to the audiological benefit and also quality of life factors underlines the important interplay between as early as possible hearing rehabilitation and the children's age‐related social development, hence language development and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Active implants with direct bone conduction without skin penetration (Osia ® , BoneBridge TM ) are currently FDA approved for patients 12 years of age and older. At the time of this writing, successful implantation in younger patients has been reported both in and outside of the United States ( 21 , 22 ). These provide optimal hearing amplification without penetrating the skin.…”
Section: Management Recommendationsmentioning
confidence: 99%